Intracardiac Metastasis From Non-Small Cell Lung Cancer - Verma, Vivek; Talmon, Geoffrey A.; Zhen, Weining K. (Frontiers in Oncology, 2015)
A 56-year-old female with history of stage IIA adenosquamous lung carcinoma treated 13 months prior to presentation with lobectomy, mediastinal lymph node dissection, and adjuvant chemotherapy, presented for several weeks of worsening dyspnea. Exam was nonfocal aside from tachycardia. Computed tomography of the chest revealed a large 4 cm x 5 cm mass in the bilateral ventricular myocardium. There was also evidence of metastatic disease elsewhere in the body, including a supraclavicular lymph node that was positive for metastatic adenosquamous lung carcinoma. She started whole heart radiotherapy and was to commence chemotherapy but passed away. This report discusses important aspects of diagnosis of this not uncommon condition that many oncologists may come across. We also discuss differential diagnosis of an isolated intracardiac mass as first-diagnosis presentations, and discuss the great importance of multidisciplinary cardio-oncologic management and clinical prioritization.